2021
DOI: 10.1111/ajt.16231
|View full text |Cite
|
Sign up to set email alerts
|

Brain death-induced lung injury is complement dependent, with a primary role for the classical/lectin pathway

Abstract: In brain‐dead donors immunological activation occurs, which deteriorates donor lung quality. Whether the complement system is activated and which pathways are herein involved, remain unknown. We aimed to investigate whether brain death (BD)‐induced lung injury is complement dependent and dissected the contribution of the complement activation pathways. BD was induced and sustained for 3 hours in wild‐type (WT) and complement deficient mice. C3−/− mice represented total complement deficiency, C4−/− mice represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our study, we found that estradiol could reduce complement activity until the C3 level, which is explained by the existence of an estradiol-responsive element in the promoter region (19). A lower complement system activity will increase lung transplant success (12,13). Indeed, by reducing C3, estradiol may inhibit actions of the active fragments such as C3a and C5a, which cause tissue damage by microvascular changes in flow and permeability, leukocyte extravasation, and migration (20).…”
Section: ' Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our study, we found that estradiol could reduce complement activity until the C3 level, which is explained by the existence of an estradiol-responsive element in the promoter region (19). A lower complement system activity will increase lung transplant success (12,13). Indeed, by reducing C3, estradiol may inhibit actions of the active fragments such as C3a and C5a, which cause tissue damage by microvascular changes in flow and permeability, leukocyte extravasation, and migration (20).…”
Section: ' Discussionmentioning
confidence: 76%
“…Thus, understanding the long-term role of estradiol in female lung donors can contribute to therapeutic donor management aiming to improve transplant outcomes. In this sense, the evaluation of estradiol's influence on the complement system activity, which increases BD-induced lung injury and worsens transplant outcomes (12,13), as well as on the inflammatory response with activated neutrophil and macrophage release of inflammatory mediators, is relevant. Therefore, in this study, we investigated the effect of estradiol on BD-induced lung inflammation, focusing on the long-term inflammatory repercussions and complementary elements as a means to understand estradiol as a possible therapeutic tool for lung transplantation.…”
Section: ' Introductionmentioning
confidence: 99%
“…Complement activation involves the activation of C3 through three pathways: the classical (CP), alternative (AP), and lectin pathways (LP). All three pathways lead to C3 activation [ 13 ], followed by the formation of C5b-9, also known as the membrane attack complex. C5b-9 forms lytic pores on the outer membranes of target cells, leading to host cell lysis [ 14 ].…”
mentioning
confidence: 99%